Mapping of workflow in clinical engineering: The experience of the University Hospital, Faculty of Medicine of Ribeirão Preto, University of São Paulo - Gomes, André FMM.; Faustino, Gabriela G; Tonani, Monique; Porcincula, Sídney; Somera, Sílvio C; Beicker, Wilker; Pazin-Filho, Antônio (Medicina (Ribeirao Preto), 2015)
The incorporation of medical devices and other technological resources with high aggregate value increases the challenges to achieve an efficient and quality management by Health Organizations. In this context, the use of tools to support the management becomes essential for the efficient use health resources in order to achieve greater stability and sustainability of the system as a whole. Thus, this study aimed to develop a mapping workflow of activities in the Clinical Engineering sector, responsible for managing medical diagnostic equipment at HCFMRP-USP, exposed in flow chart form, aiming later incorporation and spread among other hospital departments.